Consumers' preference and market segmentation in developing countries : rice marketing in Tanzania - Mgendi, G.S.; Mujawamariya, Gaudiose; Isinika, A.C. (2018)
The study analysed quality attributes that determine consumers' preference and demand for food by taking the case of rice consumption. This study also explored the segmentation of the rice market in Tanzania based on the rice products' attributes. Surveys and conjoint ranking exercises were conducted with 300 rice consumers randomly selected in Dar es Salaam and Morogoro markets in Tanzania. The conjoint analysis intended to assess the importance of preference attributes for rice products and simulate the preference market share. Subsequently, a cluster analysis identified consumer segments in the market, and a multinomial logit model was used to analyse the influence of socioeconomic characteristics on the probability of fitting into a particular segment. The results revealed that aroma, non-broken rice grains, and cleanness are key preference attributes. Three consumer segments were identified: consumers who received quality cues from the origin and were also price-driven, consumers who pursued aroma as the prime quality attribute, and consumers who explored all quality aspects. The illustrative segments indicate the possibility of identifying market niches and, consequently, orient rice production, processing and marketing, to target the preferences and needs of such niches. Producers must invest in the production of aromatic varieties because aroma remains the key attribute preferred in Tanzania. Traders and processors must invest in advanced technology to improve the cleanness of rice and reduce the proportion of broken rice. The government and development partners must support research to promote the attributes desired in rice markets.